Analisa Pengaruh Entrepreneurial Education Terhadap Entrepreneurial Intention Dengan Menggunakan Fintech Adoption Sebagai Variabel Intervening pada Mahasiswa Jurusan Bisnis-Manajemen - Virza Utama Alamsyah; Serlie Erna Putri; Rexsalvador Yana; AGUS PURWANTO (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
This study aims to measure the entrepreneurial intention among business school student in Jakarta, Indonesia .The numbers of unemployment raise significantly in recent years especially who graduate with business management major. This article presents the effect of Entrepreneurial Learning to Entrepreneurial Intention with Fintech Adoption as intervening variables. The results showed that Entrepreneurial learning is the  strongest factors which affected competitiveness, but fintech adpotion could motivate student to start a new business after they studied Entrepreneurship. The model was tested using SEM- Path Analysis. A total of 64 valid questionnaires were collected from snowball sampling. This paper addresses the topic in a strategic and managerial point of view, and it can be used in entrepreneurial studies particularly those relating to entrepreneurial intention and financial technology